Bibliometric analysis of research on Alzheimer’s disease and non-coding RNAs: Opportunities and challenges - Fei, Xinxing; Wang, Shiqi; Li, Jiyang; Zeng, Qiu; Gao, Yaqian; Hu, Yue (Frontiers in Aging Neuroscience, 2022)
Background: Non-coding RNAs (ncRNA) are a kind of RNA that does not encode protein, which play an important role in Alzheimer’s disease (AD). However, there is a lack of bibliometric analysis and visualization analysis of the research related to AD and ncRNAs. Materials and Methods: Literature related to AD and ncRNAs in the last decade were searched through the Web of Science Core Collection (WOSCC). The relevant information from all the searched articles was collected. The bibliometric visualization website, CiteSpace, and VOSviewer were used for visualization analysis of countries/ regions, institutions, authors, and keywords. Results: In total, 1,613 kinds of literature were published in the field. Literature in this field were published in 494 journals. The Journal of Alzheimer's Disease was the most popular journal. China, Louisiana State University System, and Lukiw WJ were the countries/regions, institutions, and authors with the highest scientific productivity, respectively. The research hotspots in this field focused on the role and mechanism of ncRNAs, especially microRNAs, in AD. The level of research was mainly based on basic research, focusing on animal and cellular levels, and related to proteomics. “Circular RNAs,” “regulation of neuroinflammation,” and “tau protein” were the future research directions. Conclusions: Taken together, the field of AD and ncRNAs is developing well. The research hotspots and frontiers in this field can provide a reference for researchers to choose their research direction.